Hemipenial morphology in the North American snake genus Phyllorhynchus (Serpentes: Colubridae), with a review of and comparisons with natricid hemipenes - Cadle, John E. (Zootaxa, 2011)
Hemipenes of species in the North American colubrid genus Phyllorhynchus are described. Contrary to previous reports of a divided sulcus spermaticus, both species have an unusual morphology in which the lips of the sulcus diverge near the apex so that the sulcus groove opens into an extensive apical nude region. Two distinctive hemipenial morphologies were discovered within P. browni, which may signal unresolved systematic issues. Phyllorhynchus hemipenes are additionally unusual for colubrids in having calyces reduced (P. decurtatus) or absent (P. browni). These features resemble some natricid hemipenes, which are reviewed in order to make detailed comparisons. That review led to a reassessment of some hemipenial characters of natricids and the recognition of several novelties, including calyces in Rhabdophis and a peculiar lobular pocket in Xenochrophis cerasogaster. I conclude that the resemblance of the sulcus configurations in Phyllorhynchus and natricids is only superficial and therefore convergent. Other evidence supports the phylogenetic placement of Phyllorhynchus with Colubridae, for which the sulcus configuration, highly reduced calyces, and extensive apical nude areas are unusual. Relationships of Phyllorhynchus within Colubridae are unclear, but the genus shares with Salvadora an unusual morphology of the rostral scale and nude hemipenial apices. However, in other respects Salvadora and Phyllorhynchus differ greatly in morphology and ecology.